SYMBOL IN DAN BROW’S THE DA VINCI CODE - Yerdian Paparo; Elizabeth Z. Oroh; Merlin Maukar (Program Studi Pendidikan Bahasa Inggris, 2022)
Reading novel can provide a lot of inspiration to become better and moren capable of solving life’s problems. So that least the reader for himself and also for others, so that it can positively change the future of the world for the better. This study aims to study the symbols of Dan Brown's novel The Da Vinci Code. The two research questions that guided this research are: 1. What are the symbols described by the author in the Da Vinci Code? 2. How does the author describe the Da Vinci Code symbols? The research method for this study was qualitative descriptive analysis, which was used as a data analysis method. As a result, it was found that the novel has two symbols, a universal symbol and a conventional symbol. A universal symbol described as follows: Vitruvian Man, The Last Supper. Five-pointed star, mona Lisa, rose line. The traditional symbol is described as follows: The Holy Grail. This study focuses on the explanation of symbols and their meanings